The Implementation of the ECM Model to Measure Inflation in Indonesia and Its Implications for State Financial Planning: Inflation, Financial Planning - Tazkia Ayu Lutvia; M. Irwan; Muhamad Baiul Hak (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of money supply, exchange rates, interest rates, and world oil prices on inflation in Indonesia and its implications for national financial planning, with the hypothesis that these monetary and external variables have a short-term and long-term relationship with domestic inflation. The study uses a quantitative design with monthly secondary data for the 2015-2024 period sourced from the Central Statistics Agency and related institutions. The analysis method used is the Engle-Granger Error Correction Model to identify short-term dynamics and long-term equilibrium between variables. The estimation results show that in the short term, the money supply and world oil prices have a non-significant negative effect, while the exchange rate and interest rates also have a non-significant negative effect on inflation. In the long term, the money supply continues to have a non-significant negative effect, while the exchange rate, interest rates, and world oil prices have a non-significant positive effect. These findings indicate that inflation in Indonesia during the observation period was more influenced by structural factors than monetary variables. Therefore, it is necessary to strengthen monetary and fiscal policy coordination, exchange rate stability, and measured energy subsidy management to support sustainable state financial planning. Keywords: Inflation, ECM, World Oil Prices, Monetary Policy, Fiscal Policy.